(untitled) (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
Financial recording practices at Matahari CCTV Semarang were previously carried out using semi-manual methods, which often caused inconsistencies between transaction records, delays in reporting, and difficulties in monitoring receivables and payables. This condition indicates the need for a more integrated and efficient accounting system. This study aims to develop and implement a web-based accounting information system using an accrual basis approach. The research adopts a Research and Development (R&D) method, starting from field observations and interviews to identify user requirements, followed by system design, development, and functional testing using black-box techniques. The implementation results show a noticeable improvement in operational efficiency. The time required for transaction recording decreased significantly, and the level of recording errors was reduced. In addition, the system enables automatic journal generation and real-time financial reporting, which improves data accuracy and accessibility. The application of the accrual basis also provides a more realistic representation of financial conditions, particularly in managing receivables and payables. Overall, the developed system demonstrates practical value for SMEs transitioning from manual to digital accounting processes, especially in improving the quality of financial information used for decision-making.